O OBJETO LITIGIOSO DO PROCESSO JUDICIAL PREVIDENCIÁRIO - Rodrigues, Enrique Feldens (Revista da AJURIS, 2012)
THE SUBJECT MATTER OF THE CONTROVERSY IN SOCIAL SECURITY LAWSUITS RESUMO: O presente artigo estuda a definição do objeto litigioso no tocante aos processos judiciais previdenciários, examinando a sua evolução e propondo uma nova perspectiva por meio da qual poderia ser compreendido no contexto do Estado constitucional democrático. A seguir analisa as consequências da delimitação do objeto litigioso na prova, na sentença e na identidade de ações, especialmente em relação à coisa julgada. PALAVRAS-CHAVE: Objeto litigioso do processo; processo previdenciário. ABSTRACT: This article studies the definition of the subject matter of the controversy regarding social security lawsuits, examining its evolution and proposing a new perspective through which it could be understood in the context of the democratic constitutional State. Then it analyses the effects of delimitation of the subject matter of the controversy on evidence, judgment and identity of claims, specially concerning res judicata. KEYWORDS: Subject matter of the controversy; social security lawsuits. SUMÁRIO: Introdução; 1 As definições de objeto do processo e de objeto litigioso do processo – Da Alemanha ao Brasil; 2 As concepções atuais – O objeto litigioso do processo previdenciário; 3 Uma compreensão global do objeto do processo previdenciário;4 A repercussão da delimitação do objeto litigioso na prova;5 A repercussão da delimitação do objeto litigioso na sentença;6 A repercussão da delimitação do objeto litigioso na identidade de ações, em particular no tocante à coisa julgada; Conclusão; Referências. SUMMARY: Introduction; 1 The definition of the subject matter of the controversy – From Germany to Brazil; 2 Present meanings given to the subject matter of the controversy in social security lawsuits; 3 A global perspective of the subject matter of the controversy in a social security lawsuit; 4 Effects of delimitation of the subject matter of the controversy on evidence; 5 Effects of delimitation of the subject matter of the controversy on judgment; 6 Effects of delimitation of the subject matter of the controversy on identity of claims, particularly regarding to res judicata; Conclusion; References.